Le virus Ebola : un révélateur d’inégalités biomédicales et une intervention internationale hétérogène - Donna A. Patterson (Anthropologie & Santé)
The 2014 West African Ebola epidemic differed considerably from previous Ebola epidemics in scope and spread. This paper draws from historical and ethnographic methodologies to contextualize the 2014 Ebola outbreak. I argue that the 2014 Ebola outbreak was unprecedented in multiple ways and that Senegal and Nigeria were able to respond much more swiftly and successfully than the three countries at the epicenter—Liberia, Sierra Leone, and Guinea—because of their more advanced healthcare systems. I seek to unpack the basis for these disparities in biomedical, political, and social responses to the epidemic and to suggest recommendations for the future.